Exploring the difficulties to improve minimally invasive application with long PHILOS plate in multifocal metadiaphyseal fractures of the proximal humerus: analysis of intraoperative procedure and clinical outcomes - Touloupakis, Georgios; Di Giorgio, Luigi; Bibiano, Luigi; Biancardi, Elena; Ghirardelli, Stefano; Dell'Orfano, Michele; Sinno, Ennio; Cera, Gianluca; Antonini, Guido; Crippa, Cornelio (Acta Biomedica Atenei Parmensis, 2019)
The MIPO (Minimally Invasive Plate Osteosynthesis) technique for treating metadiaphyseal fractures of the proximal humerus has gained great attention during the past years. The purpose of this retrospective study was to underline all the important difficulties when the MIPO technique is applied, to propose practical solutions and to evaluate the overall clinical outcome of our patients treated with this technique. A total of 14 patients had been operated in two different surgical units, at San Carlo Borromeo Hospital (Milan, Italy - 11 patients) and in Policlinico Umberto I Hospital (Rome, Italy - 3 patients), between June 2013 and November 2016. The humeral fractures were divided according to the Maresca et al. classification system. A lateral deltoid-split or an anterolateral deltopectoral approach was performed in the proximal humerus. In distal approach, an anterior or a lateral window was performed for plate fixation. After a follow-up of 17,4 (range 3-31) months all patients showed fracture healing and there were no non-unions or infected cases. MIPO of the humerus is a tissue sparing technique and in expert hands can improve healing rates and can also reduce complications like nerve damages and infections. In conclusion, we would like to highlight the importance of the MIPO technique as a possible alternative option to the traditional ORIF technique.